Thermodynamic evaluation of utilizing different ice thermal energy storage systems for cooling application in office buildings in Malaysia - Rismanchi, Behzad; Saidur, Rahman; Masjuki, Haji Hassan; Mahlia, Teuku Meurah Indra (Elsevier, 2012)
Storage can establish balance between production and demand consumption level in almost all the energy conversion systems. The same principle is valid for cooling applications, especially when the system is supposed to operate daily during the year. This is the condition that exists in tropical climate of Malaysia. The statistical data shows that almost one-fourth of the AC energy use in the country is due to office buildings. Therefore, utilizing the cold thermal energy storage (CTES) technique can significantly reduce the energy demand. In this study, a macroscopic thermodynamic analysis of the application of five different CTES systems for an office building in Malaysia is presented. The building energy usage is recorded and the average pattern is applied for chiller selection, storage tank sizing and finally energy and exergy evaluation. The results show that all the systems are highly efficient in terms of energy with the minimum of 93 for ice harvesting and maximum of 98 for encapsulated technique. However, the exergetic evaluation implies a totally different scenario of the study. The maximum exergy efficiency is for ice on coil (internal) technique with an amount of 18. It was also found that increasing the room set-point temperature by 5 Â°C can reduce the exergy efficiency by 4.